Dysregulated cytokine expression in lesional and nonlesional skin in hidradenitis suppurativa. (17th November 2015) - Kelly, G.; Hughes, R.; McGarry, T.; van den Born, M.; Adamzik, K.; Fitzgerald, R.; Lawlor, C.; Tobin, A.M.; Sweeney, C.M.; Kirby, B.
Summary: Background: There is a dearth of information on the precise pathogenesis of hidradenitis suppurativa (HS), but immune dysregulation is implicated. Objectives: To determine the nature of the immune response in HS. Methods: Skin biopsies – lesional, perilesional (2 cm away) and uninvolved (10 cm away) – were obtained from patients with HS and healthy controls. The expression of various cytokines was determined by enzyme‐linked immunosorbent assay, flow cytometry and real‐time polymerase chain reaction. Results: The expression of the inflammatory cytokines interleukin (IL)‐17, IL‐1β and tumour necrosis factor‐α was enhanced in lesional skin of patients with HS. In addition, IL17A and IL1B mRNA were enhanced in clinically normal perilesional skin. CD4 + T cells produced IL‐17 in HS, while CD11c + CD1a − CD14 + cells were sources of IL‐1β. Activated caspase‐1 was detected in HS skin and was associated with enhanced expression of NLRP3 and IL18 . Inhibition of caspase‐1 decreased IL‐1β and IL‐18 production, suggesting that the caspase‐1 pathway participates in IL‐1β and IL‐18 expression in HS. Abnormal cytokine expression was detected in perilesional and uninvolved skin, which may suggest that subclinical inflammation is present in HS skin prior to the formation of an active lesion. Conclusions: This study demonstrates that CD4 + T cells produce IL‐17 in HS and that the IL‐17 pathway may be important in HS pathogenesis. CD11c + CD1a − CD14 + cells are a source of IL‐1β in HS, the production of which was shown to be mediated, in part, via a caspase‐1‐dependent pathway. These results suggest that IL‐17 and the caspase‐1‐associated cytokines IL‐1β and IL‐18 may play a role in the pathogenesis of HS. Abstract : What's already known about this topic? Immune dysregulation is involved in hidradenitis suppurativa (HS). What does this study add? This study is the first to demonstrate the expression of interleukin (IL)‐17 in nonlesional skin of patients with HS. We show that CD11c + CD1a − CD14 + cells produce IL‐1β in HS and demonstrate that activated caspase‐1 and IL‐18 are present in HS skin. This suggests that IL‐17 and the caspase‐1‐associated cytokines IL‐1β and IL‐18 may play a role in the pathogenesis of disease. Linked Comment: Prens, et al. Br J Dermatol 2015; 173: 1361